2021
DOI: 10.1021/acs.jmedchem.0c01664
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors Targeting Biosynthesis of Ceramide, the Central Hub of the Sphingolipid Network

Abstract: Ceramides are composed of a sphingosine and a single fatty acid connected by an amide linkage. As one of the major classes of biologically active lipids, ceramides and their upstream and downstream metabolites have been implicated in several pathological conditions including cancer, neurodegeneration, diabetes, microbial pathogenesis, obesity, and inflammation. Consequently, tremendous efforts have been devoted to deciphering the dynamics of metabolic pathways involved in ceramide biosynthesis. Given that seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 151 publications
(308 reference statements)
0
20
0
Order By: Relevance
“…Targeting enzymes that generate ceramide and S1P to restore a rheostat of ceramide-S1P have been considered as a therapeutic strategy in various diseases (reviewed in [ 283 , 284 ]). In the same line, the application of compounds that can reduce the ratio of ceramide/S1P by targeting the enzymes involved in ceramide production and SphKs would be beneficial to prevent oxidant-induced kidney injury ( Table 4 ) [ 27 , 43 , 62 , 66 , 71 , 74 , 75 , 76 , 78 , 85 , 94 , 198 , 200 , 207 , 219 , 226 , 260 , 264 , 281 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 ].…”
Section: A Rheostat Of Ceramide-s1p In the Regulation Of Oxidative St...mentioning
confidence: 99%
“…Targeting enzymes that generate ceramide and S1P to restore a rheostat of ceramide-S1P have been considered as a therapeutic strategy in various diseases (reviewed in [ 283 , 284 ]). In the same line, the application of compounds that can reduce the ratio of ceramide/S1P by targeting the enzymes involved in ceramide production and SphKs would be beneficial to prevent oxidant-induced kidney injury ( Table 4 ) [ 27 , 43 , 62 , 66 , 71 , 74 , 75 , 76 , 78 , 85 , 94 , 198 , 200 , 207 , 219 , 226 , 260 , 264 , 281 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 ].…”
Section: A Rheostat Of Ceramide-s1p In the Regulation Of Oxidative St...mentioning
confidence: 99%
“…A study in mice by Bhat et al demonstrated that ceramide plays a critical role in phenotype transition and mineral deposition in arterial smooth muscle cells leading to arterial medial calcification and increased PWV [ 129 ]. Further, attempts to alleviate vascular dysfunction and atherosclerosis via ceramide synthesis inhibition in animal models have been encouragingly successful [ 130 , 131 , 132 ].…”
Section: ‘Arteriometabolomics’ Approachmentioning
confidence: 99%
“…The chemical structure of ceramides consists of a sphingoid base (e.g., dihydrosphingosine, sphingosine, phytosphingosine or 6-hydroxy sphingosine), which is a long-chain amino alcohol, and one among several fatty acids, different in chain length and degree of saturation, joined by an amide linkage (Figure 1) [20]. The addition of polar groups results in sphingolipid classes that vary in their underlying ceramide, whereas the addition of variable sugar groups results in different glycosphingolipids, adding a further level of complexity and heterogeneity [20]. There are three major pathways by which ceramides are synthesized (Figure 2) [21,22]:…”
Section: Chemical Structure and Productionmentioning
confidence: 99%